Ecological Factors Mediate Immunity and Parasitic Co-Infection in Sea Fan Octocorals - Tracy, Allison M.; Weil, Ernesto; Burge, Colleen A. (Frontiers in Immunology, 2021)
The interplay among environment, demography, and host-parasite interactions is a challenging frontier. In the ocean, fundamental changes are occurring due to anthropogenic pressures, including increased disease outbreaks on coral reefs. These outbreaks include multiple parasites, calling into question how host immunity functions in this complex milieu. Our work investigates the interplay of factors influencing co-infection in the Caribbean sea fan octocoral, Gorgonia ventalina, using metrics of the innate immune response: cellular immunity and expression of candidate immune genes. We used existing copepod infections and live pathogen inoculation with the Aspergillus sydowii fungus, detecting increased expression of the immune recognition gene Tachylectin 5A (T5A) in response to both parasites. Cellular immunity increased by 8.16% in copepod infections compared to controls and single Aspergillus infections. We also detected activation of cellular immunity in reef populations, with a 13.6% increase during copepod infections. Cellular immunity was similar in the field and in the lab, increasing with copepod infections and not the fungus. Amoebocyte density and the expression of T5A and a matrix metalloproteinase (MMP) gene were also positively correlated across all treatments and colonies, irrespective of parasitic infection. We then assessed the scaling of immune metrics to population-level disease patterns and found random co-occurrence of copepods and fungus across 15 reefs in Puerto Rico. The results suggest immune activation by parasites may not alter parasite co-occurrence if factors other than immunity prevail in structuring parasite infection. We assessed non-immune factors in the field and found that sea fan colony size predicted infection by the copepod parasite. Moreover, the effect of infection on immunity was small relative to that of site differences and live coral cover, and similar to the effect of reproductive status. While additional immune data would shed light on the extent of this pattern, ecological factors may play a larger role than immunity in controlling parasite patterns in the wild. Parsing the effects of immunity and ecological factors in octocoral co-infection shows how disease depends on more than one host and one parasite and explores the application of co-infection research to a colonial marine organism.